(untitled) (Journal of the College of Education for Women, 2020)
Racism changes its meaning, shape, purpose or function according to various factors such as time, place, motives, and backgrounds; among others. It seems, however, to have deep roots back in the history of mankind. Such a concept stems from a perceived difference with the other. It is fed by the feeling of being hierarchically superior in opposition to another party that is depicted as inferior. Since ancient times, racism is disguised in different forms and manifests itself on various levels. It is a truism that this ideology can be best presented via language. Due to its negative implication, racism lends itself to a critical kind of research. As such, this paper is a critical pragmatic investigation for this phenomenon as conceptualized in the Glorious Quran. Critical pragmatics focuses on how the pragmatic theories scrutinize the reflection of a negative issue in language where aspects of power or ideology are highlighted. These theories, in turn, provide the pragmatic strategies that underpin the illegitimate issue under investigation. This paper sets for itself the task of answering these questions: How is racism manifested in the Glorious Quran by the unbelievers? What are the pragmatic theories that are utilized to impart this notion? It aims at finding out the manifestations of racist ideology in the Glorious Quran and discovering the pragmatic theories utilized to convey racism. It is hypothesized that racism is realized explicitly and implicitly.